Analysis of Copper and Lead in Nata de Coco - Annida Fadlila Hanan; Jahra Najdah Alfiah; Safira Rizqi Annisa; Hindun Hindun (Universitas Negeri Yogyakarta, 2023)
The content of heavy metals in nata de coco has become a polemic in Indonesia due to the use of fertilizers such as urea, NPK, and ZA as a source of nitrogen and it is feared that it will leave residues in nata de coco products. The purpose of this study was to analyze the levels of heavy metals Cu and Pb in branded and bulk nata de coco. Samples were analyzed using AAS. The results of the analysis showed that the Cu content in branded and bulk nata de coco was the same, which is 0.00096 mg/g. The Pb content in branded nata de coco was not detected, but in bulk nata de coco it was found to be 0.0409 mg/g. Pb content far exceeds the threshold of SNI 01-4317-1996.